AI Technologies, Privacy, and Security - Elliott, David; Soifer, Eldon (Frontiers in Artificial Intelligence, 2022)
Privacy remains one of the most recurrent concerns that people have about AI technologies. The meaning of the concept of “privacy” has proven to be fairly elusive. Accordingly, the concerns people have about privacy are often vague and ill-formed, which makes it correspondingly difficult to address these concerns, and to explain the ways in which AI technologies do or do not pose threats to people's interests. In this article, we draw attention to some important distinctions that are frequently overlooked, and spell out their implications for concerns about the threats that AI-related technology poses for privacy. We argue that, when people express concerns about privacy in relation to AI technologies, they are usually referring to security interests rather than interests in privacy per se. Nevertheless, we argue that focusing primarily on security interests misses the importance that interests in privacy per se have through their contribution to autonomy and the development of our identities. Improving insight about these issues can make it easier for the developers of AI technologies to provide explanations for users about what interests are and are not at stake through the use of AI systems.